Variasi Data Suhu Permukaan Laut, Tinggi Paras Laut, Klorofil-a, dan Upwelling di Perairan Selatan Jawa serta Korelasinya Dengan Data Lapangan - Herlambang Aulia Rachman; Jonson Lumban Gaol; Fadli Syamsudin (Journal of Marine and Aquatic Sciences, 2019)
South Java Sea are regions that have quite complex dynamics because they are influenced by several factors, both regionally and globally. The influence certainly affects the variations in oceanographic features such as Sea Surface Temperature (SST), Sea Surface Height (SSH), and Chlorophyll-a concentration. Observation of oceanographic feature at this time has many methods, one of them by remote sensing. The purpose of this study is to calculate the variation of oceanographic conditions based on satellite data and its correlation with field data. The results show that the SPL and ATPL data with the field data have a fairly good relationship, where the value of R2 reaches 0.74 and 0.9. In general, the variation of oceanographic data has the same pattern that is changing seasonally. SST and SSH data are at their maximum in the January-March period, while the minimum is July-September. While the concentration of chlorophyll-a is at the maximum condition in July-September and minimum in January-March. This is thought to be an upwelling phenomenon that occurred in July-September due to the monsoon wind movement. Upwelling index calculation results based on wind data show that in the period June to September is the peak of the upwelling phenomenon.